The Effect Of Information Technology And Perceived Risk In Anticipating Tax Evasion - Adelheid Gracelia Fiero Paoki; Jesica Delya Yusha; Steven Emanuel Kale; Yenni Mangoting (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study aimed to determine tax evasion dynamics under the risk perception of using tax information technology. The study also investigated perceived risk as a moderating variable in the relation between information technology (IT) and tax evasion. One hundred questionnaires were collected from individual taxpayers and analysed using Partial Least Squares (PLS). The result showed that IT could reduce tax evasion. The moderating test result also discovered that taxpayers' risk perception could increase IT usage to reduce tax evasion. These results highlighted that society's acceptance of information technology is more of an effort to do taxation duties that would help them avoid tax inspection and penalty. Risk is believed to be attached to IT, and so eases review and detection of tax fraud, consideration by the taxpayer when tax evasion. That signifies tax authorities' success in modernizing tax administration to minimize tax evasion while increasing tax service quality by optimizing information technology usage. Therefore, these findings serve as a reference for the tax authorities to enact reforms in sustainable information technology to simplify tax administration, improve taxpayers' services and law enforcement.